PERANCANGAN APLIKASI GOIZUU UNTUK PEMBELAJARAN SHKYUU GOI - Putri Pratiwi; Soni Mulyawan Setiana (Fakultas Ilmu Budaya, Universitas Komputer Indonesia, 2022)
This paper entitled “Goiizu Application Design for Shokyuu Goi Learning” is aimed to determine the design of the Goiizu application as a basic Japanese vocabulary learning or Shokyuu Goi. Goiizu Media was created using Adobe Flash Professional CS6. The method used in this research is the ADDIE model development method (Analysis, Design, Development, Implementation, and Evaluation). The explanation in Goiizu media design consists of several steps, such as the design of the opening display to the profile menu. Media Goiizu discusses basic Japanese vocabulary with material taken from the book NIHONGO KIRAKIRA Class X. The conclusion from this research is that the design of the Goiizu application for learning Shokyuu Goi vocabulary has been successfully carried out. Keywords: Goiizu, Adobe Flash, ADDIE, Application, Shokyuu Goi